Pattern transferring of Prolift-100 polymer sacrificial layers with controlled sidewall profile. (14th May 2021) - Silva, Jorge R; Kala, Hemendra; Tripathi, Dhirendra K; Papanastasiou, Kirsten; Silva, K K M B Dilusha; Putrino, Gino; Martyniuk, Mariusz; Keating, Adrian; Antoszewski, Jarek; Faraone, Lorenzo
Abstract: While wet pattern transferring of polymers is faster than dry processing, it can lead to excessive undercut that will erode and distort features in patterned sacrificial regions during micro electro mechanical systems (MEMSs) fabrication. Dry etching processes based on O2, CF4 and N2 chemistry reduce undercutting of features to around 2 µ m, but the resulting sidewall profiles of the patterned polymer islands are generally unsuitable for subsequent conformal deposition of thin films for surface micromachined MEMS fabrication. This paper presents a dry etching process for Prolift-100-16 polymer sacrificial layers, that employs a combination of a hard mask and a subsidiary sacrificial layer, that overcomes the limitations of undercut control and conformal deposition of physical vapour deposition techniques. The dry etching process is optimized to reduce the feature undercut to as low as 1 µ m, while also producing sidewall profiles suitable for subsequent conformal deposition of thin films.